Chelation of neurotoxic zinc levels does not improve neurobehavioral outcome after traumatic brain injury - Hellmich, Helen L. (2008)
Increases of synaptically released zinc and intracellular accumulation of zinc in hippocampal neurons after traumatic or ischemic brain injury is neurotoxic and chelation of zinc has been shown to reduce neurodegeneration. Although our previous studies showed that zinc chelation in traumatically brain-injured rats correlated with an increase in whole-brain expression of several neuroprotective genes and reduced numbers of apoptotic neurons, the effect on functional outcome has not been determined, and the question of whether this treatment may actually be clinically relevant has not been answered. In the present study, we show that treatment of TBI rats with the zinc chelator calcium EDTA reduces the numbers of injured, Fluoro-Jade- positive neurons in the rat hippocampus 24 hours after injury but does not improve neurobehavioral outcome (spatial memory deficits) two weeks post-injury. Our data suggest that zinc chelation, despite providing short-term histological neuroprotection, fails to improve long-term functional outcome, perhaps because long-term disruptions in homeostatic levels of zinc adversely influence hippocampus-dependent spatial memory.